The Effects of Procedural Justice on Obligation to Obey, and Compliance among Incarcerated Offenders in South Africa - Bello, Paul Oluwatosin (The prison journal, 2022)
This study explores the impacts of procedural justice on incarcerated offenders’ obligation to obey, and compliance with correctional rules and procedures in selected South African correctional centers. The Tylerian process-based regulation model holds that compliance with legal authorities is contingent upon some normative and instrumental factors. While these factors have been considered to shape compliance among inmates in correctional centers in Western societies, there is a dearth of research on compliance behavior among incarcerated offenders in correctional centers in transitional African societies, including South Africa. A cross-sectional survey of participants from selected correctional centers in South Africa assessed the effect of procedural justice and other exogenous elements on inmates’ obligation to obey and comply with correctional rules and procedures. The findings indicate, among others, that inmates who assessed correctional officials as procedurally just or fair were more likely to obey and comply with correctional rules and procedures. The implications of the findings for the effective management of incarcerated offenders are discussed.